Yukon River Basin Streamflow Forecasting System - Elshamy, Mohamed; Loukili, Youssef; Princz, Daniel; Richard, Dominique; Tesemma, Zelalem; Pomeroy, John W. (Centre for Hydrology, University Saskatchewan, Saskatoon, Saskatchewan, 2020)
Prepared for Government of Yukon, Yukon Environment, Water Resources Branch, Whitehorse, Yukon Government of Yukon Water Resources Branch The Yukon River Basin is one of the main rivers in the Arctic region of North America and is shared between Canada and the US. The Canadian part covers almost half of the Yukon Territory in addition to a small portion of the province of British Columbia, while the US part falls totally within the state of Alaska. This study is concerned with Canadian part of the Yukon River with its outlet at Eagle, just across the border in Alaska. Small parts of this catchment are in Alaska. This basin has an area of 288,000 km2, from 58.8 – 65.6°N and 129.2 – 134.1°W. The southern part of the basin is characterized by large glaciers at high elevations (up to 4700 m above sea level) with steep slopes, and thus generates considerable runoff. There are also mountain ranges on the eastern and northern boundaries of the basin, while the western areas are milder in slope and partially forested. Snow redistribution, snowmelt, glacier melt and frozen soil processes in winter and spring along with summertime rainfall-runoff and evapotranspiration processes are thus key to the simulation of streamflow in the basin. This project developed, set up, calibrated, validated, and operationalized a streamflow discharge forecasting system for the Yukon River and several of its tributary rivers within the Yukon Territory. The Yukon River Basin streamflow forecasting system is based around the MESH (Modélisation Environmentale Communautaire - Surface and Hydrology) hydrological land surface model. MESH is a state-of-the-art semi-distributed cold regions hydrological land surface model that models both the vertical exchanges of heat and moisture between the land surface and the atmosphere as well has the horizontal transfer of water to streams that is routed hydrologically to the outlet of the basin. It includes snow, frozen soil and glacier processes as well as the full suite of warm season hydrology. MESH ...